2019
DOI: 10.1016/j.ebiom.2019.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Age, lipofuscin and melanin oxidation affect fundus near-infrared autofluorescence

Abstract: BackgroundFundus autofluorescence is a non-invasive imaging technique in ophthalmology. Conventionally, short-wavelength autofluorescence (SW-AF) is used for detection of lipofuscin, a byproduct of the visual cycle which accumulates with age or disease in the retinal pigment epithelium (RPE). Furthermore, near-infrared autofluorescence (NIR-AF) is used as a marker for RPE and choroidal melanin, but contribution of lipofuscin to the NIR-AF signal is unclear.MethodsWe employed fluorescence microscopy to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 43 publications
0
35
1
Order By: Relevance
“…66,67 Previously, we have suggested that the NIR-AF emitted by lipofuscin granules and the lipofuscin moiety of melanolipofuscin granules may be mainly due to the accumulation of melanin degradation products. 68 Bisretinoids contained in lipofuscin granules in degenerating RPE cells can also undergo photo-oxidation leading to additional toxic products. These oxidized and fragmented bisretinoids might contribute to NIR-AF as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…66,67 Previously, we have suggested that the NIR-AF emitted by lipofuscin granules and the lipofuscin moiety of melanolipofuscin granules may be mainly due to the accumulation of melanin degradation products. 68 Bisretinoids contained in lipofuscin granules in degenerating RPE cells can also undergo photo-oxidation leading to additional toxic products. These oxidized and fragmented bisretinoids might contribute to NIR-AF as well.…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that these granules were lipofuscin and melanolipofuscin formed by the fusion of lipofuscin and melanin with aging and oxidative stress . Previously, we have suggested that the NIR‐AF emitted by lipofuscin granules and the lipofuscin moiety of melanolipofuscin granules may be mainly due to the accumulation of melanin degradation products . Bisretinoids contained in lipofuscin granules in degenerating RPE cells can also undergo photo‐oxidation leading to additional toxic products.…”
Section: Discussionmentioning
confidence: 99%
“…granules exhibit both SWAF and IRAF in aged human donor eyes 24 . This finding helps explain our previously published report showing co-localization of SWAF and IRAF signals in AOSLO 9 .…”
mentioning
confidence: 94%
“…Boulton and colleagues identified RPE lipofuscin as a fraction at the interface between 1.2 and 1.4 M of sucrose [21,22]. Similar fractionation methods have been adopted by other investigators to isolate RPE lipofuscin granules for lipofuscin studies, including morphological, lipid, proteomic, and melanin oxidation analyses [23][24][25][26]. The lipofuscin fraction was originally identified by fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 99%